Improvement Of Students' Competences on Folklore Genres in Distance Learning Environment - Kadirova Mashhura Nasirovna (Genius Journals, 2022)
Learning is the beginning of a need for excellence. It is clear that the more advanced the knowledge and knowledge is; the more need is required to learn and to improve its potentials. The distance learning unit is one of the alternative approaches, it can be replaced by a face-to-face or traditional training, and this is one of the main factors in the development of Higher Education. One of the scientists Holmberg describes distance education as continuous communication. So, in relation to time and place, the suffix o and the suffix o are separated from each other. It is believed that the separation of the teacher and the student at the time of training is the main feature of distance education. The article also provides opinions and comments on improving students' competences in folklore genres in the distance learning environment.
Keywords: Hybrid; folklore; folkloreimprovement